2021
DOI: 10.1002/er.6733
|View full text |Cite
|
Sign up to set email alerts
|

Biochar catalyzing polymerization of the volatiles from pyrolysis of poplar wood

Abstract: In this study, the pyrolysis of poplar wood chips with biochar catalyst produced from gasification of the same poplar wood chips was conducted, aiming to probe its influence on the evolution of the pyrolysis products. From the results, it was concluded that the biochar catalyst enhanced the polymerization of the volatiles produced from the pyrolysis, and thus reduced the yields of the gaseous compounds while increased the yield of char. The carbonaceous deposit on surface of the char was oxygen-rich and more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The carbonization temperatures of 350 to 400 °C used in this study are expected to induce dehydration, thermal decomposition, and carbonization of the large biomolecules, with molecular weight reduction and aromatic ring formation during pyrolysis. Condensed aromatic ring stacking continues developing with further temperature increases (Li et al 2021).…”
Section: Solid State Nmr Spectrummentioning
confidence: 99%
“…The carbonization temperatures of 350 to 400 °C used in this study are expected to induce dehydration, thermal decomposition, and carbonization of the large biomolecules, with molecular weight reduction and aromatic ring formation during pyrolysis. Condensed aromatic ring stacking continues developing with further temperature increases (Li et al 2021).…”
Section: Solid State Nmr Spectrummentioning
confidence: 99%
“…Studies have demonstrated the positive and pivotal roles of biochar in forestalling C degradation and increasing the C sink for an entire ecosystem [1][2][3][4]. The polycondensation caused by high-temperature pyrolysis converts the organic carbon in biomasses to aromatic carbon; this accounts for the stability of biochar [5][6][7]. The aromaticity and stability of biochar are directly related to the content of C, H, O, and N [8].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Also, there has been considerable and particular attention on biochar due to its versatile properties in various environmental applications. 23,24 Biochar is a carbon-based porous material, 21,25 and the controllable physico-chemical properties of biochars made them versatile materials in a variety of industries. For example, biochar has been widely used for soil amendment/remediation.…”
Section: Introductionmentioning
confidence: 99%